Ibuprofen against Aspirin – you first, please! Thanks go ahead…. Issue 2 (2002) - Jankowski Jankowski, Christopher K. Christopher K.; Leclair Leclair, Gaëtan Gaëtan
Abstract : Aspirin (ASA) and Ibuprofen (IBU), two common NSAIDs, seem to exert a mutual interference on the blood platelet aggregation level. We wish to clarify this controversy on the basis of crystallographic data and molecular modelling.